Aphasia elicited by electrical stimulation of the right anterior corpus callosum. Issue 3 (4th March 2019) - Völk, Stefanie; Johannböke, Maren; Noachtar, Soheyl; Vollmar, Christian
ABSTRACT: Background : The preoperative evaluation of drug-resistant focal epilepsy patients considered for epilepsy surgery provides a unique setting to evaluate cortical function and corresponding networks. Aims : Whereas there is a wealth of data on cortical language localization using electrical stimulation with subdural electrodes, there is much less experience with stimulation of depth electrodes in the white matter and an effect on language function via electric stimulation of the corpus callosum has not been demonstrated so far. Methods & Procedures : We report on a 29-year-old epilepsy patient with bilateral language representation who underwent pre-surgical EEG-video-monitoring for drug-resistant, non-lesional right frontal lobe epilepsy. Outcomes & Results : Electric stimulation of a stereotactically implanted depth electrode in the right anterior corpus callosum elicited paraphasia and anomia. The precise mechanism could be an inhibition of cortical language areas in the left hemisphere, the right hemisphere or interference with transcallosal connectivity. Conclusions : This is the first report on language dysfunction through electric stimulation in the corpus callosum, most likely through an inhibition of cortical language areas in the left frontal lobe.